2016
DOI: 10.1016/j.xjep.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The case of veterinary interprofessional practice: From one health to a world of its own

Abstract: (approx. 150 words)Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…However, despite VS's biographies being significantly longer than VNs', VS biographies included the word 'care' less often than VNs. This mirrors research suggesting VNs have a greater focus on care than VSs (Kinnison et al 2016), however this is not to suggest that VSs are unmotivated by animal care and this care could be made more explicit through their biographies. Radha et al (2012) have suggested in human healthcare that sufficient information, for example regarding specialisms, should be provided to allow clients to make an informed choice about which practice to join.…”
Section: Discussionmentioning
confidence: 49%
“…However, despite VS's biographies being significantly longer than VNs', VS biographies included the word 'care' less often than VNs. This mirrors research suggesting VNs have a greater focus on care than VSs (Kinnison et al 2016), however this is not to suggest that VSs are unmotivated by animal care and this care could be made more explicit through their biographies. Radha et al (2012) have suggested in human healthcare that sufficient information, for example regarding specialisms, should be provided to allow clients to make an informed choice about which practice to join.…”
Section: Discussionmentioning
confidence: 49%
“…A key step in moving emergency management systems from fragmentation to a position of strength and unity is to become a collaborative practice-ready emergency management workforce [ 41 , 61 ]. There is clear evidence that interprofessional education enables effective collaborative practice through attitude change, greater understanding of the roles and responsibilities of others, increased awareness of barriers across professions, and increased awareness of the importance of professional collaboration [ 61 , 62 , 63 ].…”
Section: Interprofessional Education and Trainingmentioning
confidence: 99%
“…These roles, including practice managers, receptionists, animal physiotherapists and equine dentists, are seldom the primary subject of peer-reviewed research. 8,9 If little has been written about the role of the veterinary nurse, even less has been written about 'front-of-house' (FoH) staff. There is, however, some published work on medical receptionists in human healthcare settings, [10][11][12][13][14] and similarities do exist between this role and that of veterinary receptionists.…”
Section: Introductionmentioning
confidence: 99%